Caracterização fenotípica e genotípica de cepas de Mycobacterium tuberculosis e resistentes às drogas antituberculosas Hospital Júlia Kubstschek, Minas Gerais 2001-2002 - Wanessa Trindade Clemente (2009)
In the context of the growing incidence of tuberculosis (TB) and multidrug-resistant tuberculosis (MDR-TB), the quick detection of resistance is vital, enabling effective treatment and the introduction of measures to control dissemination. The characterization of resistance to anti anti-tuberculosis drugs (anti-TB), by means of sensitivity tests and molecular studies, has gained importance over the last decades. However, its availability is compromised, especially in developing countries. This study depicted the resistance of strains of M. tuberculosis in the state of Minas Gerais to the main anti-TB drugs used, comparing genetic mutation, level of resistance, and patients clinical-epidemiological data. Clinical-epidemiological data of 160 patients with presumed TB who had been seen at the Júlia Kubitschek Hospital were assessed. Of these, 76 pulmonary samples were selected from patients with a higher risk of developing resistant TB who were submitted to an evaluation of first-line anti-TB drugs (isoniazid, rifampicin, pyrazinamide, ethambutol, and streptomycin). This assessment was made by means of (a) radiometric qualitative and quantitative sensitivity testing (ST), with the determination of the minimal inhibitory concentration (MIC); (b) genotyping by analysis of the polymorphism of sequences generated by endonucleases digestion - Restriction fragment length polymorphism (RFLP); (c) DNA sequencing of the primary genes linked to resistance (katG, ahpC, inhA, pncA, embB); and (d) PCR reverse line blot hybridization, a reverse hybridization assay for associate drifampicin resistance gene mutation (rpoB). Of the 76 samples evaluated by the sensitivity test, 24 demonstrated resistance to at least one of the anti-TB drugs tested. Patients bearing these strains displayed a greater incidence of prior TB and exposure to anti-TB drugs. The acquired resistance was four times as frequent as the primary resistance; 19 (79.0%) patients had prior exposure to the drugs and 4 (16.6%) had not. None of the resistant strains showed similar RFLP patterns, a fact that diminished the epidemiological probability of epidemiological correlation among them. Of the resistant strains, 87.5% (21/24) were resistant to isoniazid; 70.8% (17/24) to rifampicin; 54.2% (13/24) to streptomycin; 43.5% (10/23) to pyrazinamide, and 41.7% (10/24) to ethambutol. Most of the strains studied (17/24) were MDR, considering combined resistance to rifampicin and isoniazid, and about 40.0% (7/17) of these displayed no additional resistance. Of the 10 MDR strains that showed additional resistance, eight were resistant to ethambutol and to streptomycin. Resistant strains in the qualitative ST showed distinct levels of drug sensitivity in the quantitative test. The quantitative ST showed no discriminatory capacity for streptomycin resistance. Strains resistant to isoniazid displayed mutations in genes katG (75.0%) and ahpC (20.0%), and no mutations in inhA. Mutations in gene rpoB were noted in 78.6% of rifampicin-resistant isolates. The detection of mutations in genes katG and rpoB combined, identified most of the MDR strains (88.2%). Mutations of the pncA gene were identified in 62.5% of the pyrazinamide-resistant strains. As to those resistant to ethambutol, mutations were observed in embB in 71.4% of the strains. For this sampling, considering the high frequency of combined resistance, the performance of qualitative and quantitative ST proved to be valid for first-line anti- TB drugs in patients with suspected TB resistance. As to genetic analysis, we noted that the detection of patients with MDR strains in Minas Gerais would be effective in 88.2% of cases, if research of the combined mutation of genes katG and rpoB were used, furnishing earlier results than with conventional testing and a good level of correlation with an elevated MIC. Assessment of mutations in embB and pncA only identified about 60% to 70% of the strains resistant to ethambutol and pyrazinamide. Inactivity of pyrazinamidase is not a good indicator of resistance, in spite of being related to a high MIC for pyrazinamide. Thus, the use of molecular techniques seems promising for rapid identification of patients with resistant strains, with consequent clinical-epidemiological benefits.